Peranan Bagian Survei dalam Menentukan Kelayakan Konsumen Mendapatkan Kredit Motor: (Studi pada PT. Federal Internasional Finance Cabang Sidomulyo Lampung Selatan) - Suradi; Galang Pratama Erlangga (Business Perspective Journal, 2022)
This study explains the role of the survey section in determining the eligibility of consumers to get motorcycle financing (study at PT. Federal Internasional Finance Sidomulyo South Lampung Region). The survey section is an important important of the company's progress, because the survey section has the task of assessing potential customers who will apply for credit. The purpose of this study is to analyze how the role of the survey section in determining the eligibility of consumers to get a motorcycle financing, which has several indicators, including: Character (character), Capacity (capacity), Capital (capital), Collateral (collateral), and Condition (condition). This research method uses descriptive qualitative research methods and data collection through observation, documentation, and interviews. This research was conducted in the survey section at PT. Federal Internasional Finance Sidomulyo South Lampung Region. The research subjects were 6 (six) people, consisting of 1 (one) key informant and 5 (five) informants. The results of this study indicate that the role of the survey section in determining the eligibility of consumers to get motorcycle financing is in accordance with the 5C principles used to survey potential credit customers and the role of the survey section is also very important for the survival of the company. Keywords : role, survey, consumer eligibility, credit